Effect of Pinus pine wood sylvestris on cow's milk chemical composition - Mukhtarova Olga; Feyzullaev Feyzullah; Mkrtchyan Gayane; Krovikova Anna; Lashneva Irina (BIO Web of Conferences)
The study was conducted on Holstein dairy cows for 6 months at the dairy farm of APK Vokhrinka LLC. Four groups of similar cows were formed (control and three experimental) with 15 heads in each. The cows of the experimental groups received 300, 500 and 700 ml of an aqueous extract of Pinus sylvestris ExtPine® pine trunk wood daily, while the control group received a standard diet without additives. The research methods included: regular milk sampling every two weeks with subsequent analysis of its chemical composition (milk fat, protein, lactose, dry matter, casein, acetone, ketone bodies, etc.), analysis of the fatty acid composition of milk with a study of the effect of the additive on the content of saturated, monounsaturated and polyunsaturated fatty acids. Statistical processing of data was carried out to determine the reliability of differences between the groups. The aim of the study was to investigate the effect of aqueous extract from Pinus sylvestris ExtPine® pine trunk wood on the chemical composition of Holstein cow milk, and to evaluate its effect on productivity and metabolic processes in animals. Increase in milk fat and protein content: in the control group, the mass fraction of fat was 3.53%, while in the 3rd experimental group it was 4.23%. Improvement of metabolic processes in cows was observed. A decrease in the concentration of acetone and β-hydroxybutyric acid (BHB) in milk was noted in the experimental groups, which indicates the prevention of ketosis. The level of urea in the milk of cows in the experimental groups was lower than in the control group, which indicates more efficient use of nitrogen compounds. Changes in the fatty acid composition of milk were noticed. An increase in medium-chain and short-chain fatty acids was observed in the experimental groups, which improves the nutritional value of milk fat.